The Impact of Emerging Wireless Network System and Cybersecurity in A Global Community - Ele, Bassey; Adinya, Odey John; I. O, Obono (Discoveries in Agriculture and Food Sciences, 2020)
Wireless network systems and cybersecurity threats are growing faster than their mitigation measures. World Economic Forum has identified wireless network security and cybersecurity threats as its top global risks for the past eight years. This paper aims to critically examine the impact of emerging wireless network systems and cybersecurity in a global community and suggest some best countermeasures against wireless and cybersecurity threats that have been of global concern. To achieve this, the study conducted an in-depth review of wireless network security and cybersecurity. This study has presented a robust wireless security mechanism and suggests appropriate countermeasure against wireless network and cybersecurity threats that is more cost-effective in mounting attacks in the service area, and simultaneously providing higher security than basic security mechanisms.